ANALYZING THE COMPENSATION AND ITS EFFECT ON LECTURERS’ JOB SATISFACTION: A Case Study of Private Colleges in Bogor - Rully, Tutus; Moeins, Anoesyirwan; Muharram, Hari (jfpublisher, 2023)
One factor that significantly affects job satisfaction among lecturers is compensation. Compensation is categorized into three dimensions, such as direct financial, indirect financial, and non-financial. This research is descriptive-verification type, and the approach used is explanatory survey. The objective of this research is to determine the effect of compensation on job satisfaction. The sampling technique used cluster sampling proportionally at five private colleges in Bogor, which led to a total sample size of 233 respondents, including Head Lectors, Lectors, and Assistant Lectors. Descriptive and quantitative analysis was conducted based on primary data obtained from field respondents, and hypothesis testing was conducted using SEM-Lisrel 8.8 method. The results indicated that the t-statistic value was greater than the t-value (t-statistic > 1.64), and the highest loading factor was found on the non-financial compensation variable (NFIN) which had a loading factor of 1.00 with a standard factor loading (SFL) of 0.5. It indicated that compensation has a positive and significant effect on job satisfaction of lecturers in private colleges in Bogor. From the 3 dimensions that affect lecturer compensation, the non-financial dimension is the dominant dimension in forming the compensation variable construct by contributing the highest standard loading factor value.